An osteogenesis/angiogenesis-stimulation artificial ligament for anterior cruciate ligament reconstruction. (May 2017) - Li, Hong; Li, Jinyan; Jiang, Jia; Lv, Fang; Chang, Jiang; Chen, Shiyi; Wu, Chengtie
Graphical abstract: Abstract: To solve the poor healing of polyethylene terephthalate (PET) artificial ligament in bone tunnel, copper-containing bioactive glass (Cu-BG) nanocoatings on PET artificial ligaments were successfully prepared by pulsed laser deposition (PLD). It was hypothesized that Cu-BG coated PET (Cu-BG/PET) grafts could enhance the in vitro osteogenic and angiogenic differentiation of rat bone marrow mesenchymal stem cells (rBMSCs) and in vivo graft-bone healing after anterior cruciate ligament (ACL) reconstruction in a goat model. Scanning electron microscope and EDS mapping analysis revealed that the prepared nanocoatings had uniform element distribution (Cu, Ca, Si and P) and nanostructure. The surface hydrophilicity of PET grafts was significantly improved after depositing Cu-BG nanocoatings. The in vitro study displayed that the Cu-BG/PET grafts supported the attachment and proliferation of rBMSCs, and significantly promoted the expression of HIF-1α gene, which up-regulated the osteogenesis-related genes (S100A10, BMP2, OCN) and angiogenesis-related genes (VEGF) in comparison with PET or BG coated PET (BG/PET) grafts which do not contain Cu element. Meanwhile, Cu-BG/PET grafts promoted the bone regeneration at the graft-host bone interface and decreased graft-bone interface width, thus enhancing the bonding strength as well as angiogenesis (as indicated by CD31 expression) in the goat model as compared with BG/PET and pure PET grafts. The study demonstrates that the Cu-containing biomaterials significantly promote osteogenesis and angiogenesis in the repair of bone defects of large animals and thus offering a promising method for ACL reconstruction by using Cu-containing nanobioglass modified PET grafts. Statement of Significance: It remains a significant challenge to develop an artificial graft with distinct osteogenetic/angiogenetic activity to enhance graft-bone healing for ligament reconstruction. To solve these problems, copper-containing bioactive glass (Cu-BG) nanocoatings on PET artificial ligaments were successfully prepared by pulsed laser deposition (PLD). It was found that the prepared Cu-BG/PET grafts significantly stimulated the proliferation and osteogenic/angiogenic differentiation of bone marrow stromal cells (BMSCs) through activating HIF-1α/S100A10/Ca 2+ signal pathway. The most important is that the in vivo bone-forming ability of Cu-containing biomaterials was, for the first time, elucidated in a large animal model, revealing the enhanced capacity of osteogenesis and angiogenesis with incorporation of bioactive Cu element. It is suggested that the copper-containing biomaterials significantly promote osteogenesis and angiogenesis in large animal defects and thus offering a promising method for ACL reconstruction by using Cu-containing nanobioglass modification of PET grafts, paving the way to apply Cu-containing biomaterials for tissue engineering and regenerative medicine.